When Satisfaction Is Not Enough to Build a Word of Mouth and Repurchase Intention - Kusuma, I Gusti Agung Eka Teja; Yasmari, Ni Nengah Wida; Agung, Anak Agung Putu; Landra, Nengah (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
This study aims to measure the impact of service quality on word of mouth (WOM) and repurchase intention mediated by customer satisfaction. Design/methodology/approach: This cross-sectional study was conducted in all branches of Bank BPD Bali in Bali involving 91 Western Union customers at Bank BPD Bali as respondents. The research hypothesis was tested using a second order model processed by Structural Equation Modeling (SEM) analysis techniques with PLS software. Findings: Satisfaction has